Impact of shell evolution on Gamow-Teller β decay from a high-spin long-lived isomer in 127Ag - H. Watanabe (Elsevier, 2021)
The change of the shell structure in atomic nuclei, so-called “nuclear shell evolution”, occurs due to changes of major configurations through particle-hole excitations inside one nucleus, as well as due to variation of the number of constituent protons or neutrons. We have investigated how the shell evolution affects Gamow-Teller (GT) transitions that dominate the β decay in the region below 132Sn using the newly obtained experimental data on a long-lived isomer in 127Ag. The T1/2=67.5(9) ms isomer has been identified with a spin and parity of (27/2+) at an excitation energy of 1942−20+14 keV, and found to decay via an internal transition of an E3 character, which competes with the dominant β-decay branches towards the high-spin states in 127Cd. The underlying mechanism of a strong GT transition from the 127Ag isomer is discussed in terms of configuration-dependent optimization of the effective single-particle energies in the framework of a shell-model approach.